2023
DOI: 10.1111/ejn.16193
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine alleviates hippocampal neuronal loss and cognitive decline in rats undergoing open surgery under sevoflurane anaesthesia by suppressing CCAAT/enhancer‐binding protein beta

Shanshan Fu,
Xianghai Zhao,
Yingna Li
et al.

Abstract: Dexmedetomidine (Dex) may exert neuroprotective effects by attenuating inflammatory responses. However, whether Dex specifically improves postoperative cognitive dysfunction (POCD) by inhibiting microglial inflammation through what pathway remains unclear. In this study, the POCD model was constructed by performing open surgery after 3 h of continuous inhalation of 3% sevoflurane to rats, which were intraperitoneally injected with 25 μg/kg Dex .5 h before anaesthesia. The results displayed that Dex interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Cell culture and animal models of dexmedetomidine administration revealed anti-inflammatory phenotype effects (22)(23)(24)(25)243). Experiments utilizing in vitro BV-2 microglia revealed that dexmedetomidine incubation resulted in an increase in M2 polarization mediated through an increase in Akt phosphorylation (22).…”
Section: Dexmedetomidinementioning
confidence: 99%
See 2 more Smart Citations
“…Cell culture and animal models of dexmedetomidine administration revealed anti-inflammatory phenotype effects (22)(23)(24)(25)243). Experiments utilizing in vitro BV-2 microglia revealed that dexmedetomidine incubation resulted in an increase in M2 polarization mediated through an increase in Akt phosphorylation (22).…”
Section: Dexmedetomidinementioning
confidence: 99%
“…Another identified mechanism of antiinflammatory microglial polarization has been through an increase in Nrf2/HO-1 signaling resulting in inhibition of NLRP3 inflammasome activation (23). When treating mice exposed to sevoflurane, 25 μg/kg dexmedetomidine administration was found to attenuate CEBPB-mediated microglial inflammatory phenotypes (24). In a similar study, mice treated with 40 ml/kg dexmedetomidine (3.3 μg/ml) prior to LPS injection resulted in a decrease in microglial activation and in oxidative stress markers when compared to 10 ml/kg of propofol (3 mg/ml) (26).…”
Section: Dexmedetomidinementioning
confidence: 99%
See 1 more Smart Citation